THE INFLUENCE OF INCENTIVES, CAREER DEVELOPMENT AND LEADERSHIP ON THE PERFORMANCE OF EMPLOYEES OF PT. BANK OCBC NISP KENDARI BRANCH - Stefhanny, Stefhanny; Madjid, Rahmat; Supriaddin, Nofal (Penelitian dan Pengembangan Ilmu, 2024)
The purpose of this study is to find out and analyze: (1) The influence of incentives, career development and leadership on the performance of employees of PT. Bank OCBc NISP Kendari Branch; (2) The effect of incentives on the performance of employees of PT. Bank OCBc NISP Kendari Branch; (3) The effect of career development on the performance of employees of PT. Bank OCBc NISP Kendari Branch; (4) The influence of leadership on the performance of employees of PT. Bank OCBc NISP Kendari Branch. The population in this study is all employees of PT. Bank OCBc NISP Kendari Branch which totals 33 employees and at the same time is used as a respondent in this study using census techniques. The data analysis methods used in this study are descriptive analysis and inferential statistics, namely SPSS. The results of the study stated that: (1) Incentives, career development and leadership have a positive and significant effect on the performance of employees of PT. Bank OCBc NISP Kendari Branch; (2) Incentives have a positive and significant effect on the performance of employees of PT. Bank OCBc NISP Kendari Branch; (3) Career development has a positive and significant effect on the performance of employees of PT. Bank OCBc NISP Kendari Branch; (4) Leadership has a positive and significant effect on the performance of employees of PT. Bank OCBc NISP Kendari Branch